Faktor-faktor mempengaruhi prestasi pekerja mengikut perspektif pekerja. Factors Affecting Employees’ Performance based on Employees’ Perspective - Azman, Maisarah; Lai, Wei Sieng (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2021)
Organizational performance depends entirely on the performance of employees. The failure of the organization to maintain good employee performance leads to the problem of high turnover rate which in turn affects the productivity of the company and the national economy. The objective of this study is to identify the factors that influence employees’ performance among employees in the area around the Klang Valley. Primary data were obtained through questionnaire approach with a total of 139 respondents who were involved in this study. Factor analysis was used to analyze the data obtained. The results of the study found that employees think that three factors, namely motivation, workplace environment as well as training and development affect their performance. Organizations need to prioritize the need for intrinsic motivation to employees and set clear training goals to improve employees’ performance.